A MATHEMATICAL MODEL FOR THINNING RATE PREDICTION OF SHEET DOUBLE HYDRO-FORMING - Đinh Văn, Duy; Vu Duc, Quang (Journal of Applied Engineering Science, 2022)
Double sheet blank hydro-forming (DSBH) is a technology for forming hollow parts with complex shapes. The pair of workpieces is deformed and shaped by the high-pressure liquid inside. The material is thinned after hydraulic forming, which significantly affects the quality of the product, especially the fields with high requirements, such as the automotive and aerospace industry. The goal of optimizing input process parameters to ensure that the level of thinning into a product is within the allowable limit is posed by this study. This study considered blank holder force, forming fluid pressure, and relative thickness as candidate factors for optimization using Response Surface Method (RSM). The spherical parts were formed by the DSBH method of welding blank pairs of DC04 carbon steel material based on theoretical analysis, experiment solution, and experiment to verify the results. Experiments were performed with different combinations of parameters using the Box-Behnken design. This paper presented a mathematical model that helps determine material thinning rate according to these three process parameters in the hydro-forming of spherical parts from welded sheet metal pairs. The research results can be applied to control the input parameters in the DSBH to achieve the wall thickness of the spherical part as desired by the manufacturer.